The prevalence and correlates of depression before and after the COVID-19 pandemic declaration among urban refugee adolescents and youth in informal settlements in Kampala, Uganda: A longitudinal cohort study - Logie, Carmen H.; Berry, Isha; Okumu, Moses; Loutet, Miranda; McNamee, Clara; Hakiza, Robert; Musoke, Daniel Kibuuka; Mwima, Simon; Kyambadde, Peter; Mbuagbaw, Lawrence (Annals of Epidemiology, 2022)
There is scant research examining urban refugee youth mental health outcomes, including potential impacts of the COVID-19 pandemic. We examine prevalence and ecosocial risk factors of depression in the periods before and after the COVID-19 pandemic declaration among urban refugee youth in Kampala, Uganda. Data from a cohort of refugee youth (n = 367) aged 16–24 years were collected in periods before (February 2020) and after (December 2020) the WHO COVID-19 pandemic declaration. We developed crude and adjusted generalized estimating equation logistic regression models to examine demographic and ecosocial factors (food insecurity, social support, intimate partner violence) associated with depression, and include time-ecosocial interactions to examine if associations differed before and after the pandemic declaration. The prevalence of depression was high, but there was no significant difference before (27.5%), and after (28.9%) the pandemic declaration (P = .583). In adjusted models, food insecurity (aOR: 2.54; 95% CI: 1.21–5.33) and experiencing violence (aOR: 2.53; 95% CI: 1.07–5.96) were associated with increased depression, and social support was associated with decreased depression (aOR: 0.85; 95% CI: 0.81–0.89). These findings highlight the urgent need for interventions to address chronic depression, food insecurity, and ongoing effects of violence exposure among urban refugee youth in Kampala.